VD_FINDINFO Décision / 2015 / 166 vom 19. Februar 2015 - VD Tribunal cantonal (2015)
CLASSEMENT DE LA PROCÉDURE, VIOLATION D'UNE OBLIGATION D'ENTRETIEN | 217 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)